Fabrication and characterization of novel nitinol particulate reinforced aluminium alloy metal matrix composites (NiTip/AA6061 MMCs). (2021) - Chauhan, Abhishek; Vates, Umesh Kumar; Kanu, Nand Jee; Gupta, Eva; Singh, Gyanendra Kumar; Sharma, Bhupendra Prakash; Gorrepati, Srinivasa Rao
Abstract: The composites of aluminium alloy metal matrix composites (AAMMCs) are extensively used to achieve the industrial demand. The present investigation deals with the manufacturing of AAMMCs reinforced with different weight percentage of nitinol particulates (NiTip) by using the powder metallurgy (P/M) technique. The weight percentage of the NiTip reinforcement is ranging from 0%, 4%, 8%, and 12%. The hardness and surface roughness of the NiTip/AA6061 metal matrix composites (MMCs) have been tested and compared with the results available in the published source to assess the novelty of the present investigation. The morphology of the NiTip/AA6061 MMCs is characterized using scanning electron microscopy (SEM). The experiment results exhibit that the surface roughness and hardness of the AAMMCs increase with increase in the percentage of NiTip content. This can also be due to the superior matrix-reinforcement interfacial bonding. The SEM results exhibit the homogenous distribution of the NiTip in AAMMCs.